Determinants of FDI Incentive Preferences of MNEs - Rolfe, Robert J.; Ricks, David A.; Pointer, Martha M.; McCarthy, Mark (Journal of International Business Studies, 1993)
In this study, managers of U.S. firms with operations in the Caribbean region evaluated the attractiveness of twenty host country incentives. Multivariate analysis of variance was employed to determine whether incentive preferences were a function of investment characteristics. The results indicate that incentive preferences depend on the type of investment, market orientation, size of investment, geographic location, year of investment, and type of product. Furthermore, exporters considered import duty concessions to be more desirable than did investors oriented toward the local markets. These results indicate that government programs waiving import duties, such as the free trade zones of the Dominican Republic and the maquiladora program of northern Mexico, are providing the incentive deemed most important by their targeted investors.